Karakteristik Campuran AC-BC Yang Menggunakan Batu Sungai Sadang Kecamatan Duampanua Kabupaten Pinrang - Nifre Dirgahayu; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2022)
Technological developments in the field of civil engineering, especially roads, are growing rapidly along with the times. However, the lack of availability of materials used in construction is a problem that needs to be addressed. Therefore, in this study, we tested the Sadang River stone as an aggregate that could be utilized in the pavement mixture, especially the AC-BC layer by using the marshal test method with reference to the 2018 Bina Marga specification. The results obtained from this study were the stability value of 1190,28 kg. -1545,08 kg, flow 2,35 mm -3,85 mm, VIM 4,335% - 3,098%, VMA 14,64% - 18,26%, VFB 70,39% - 83,03%.